Analysis of the Implementation of Hospital Service Management and Its Impact on Outpatient Satisfaction at Rumah Sakit Haji, Medan - Meriahta Sitepu; Setia Megawati Hutajulu (Universitas Ibn Khaldun Bogor, 2026)
Patient satisfaction is an important indicator in assessing the quality of hospital services, particularly for participants of the National Health Insurance (JKN) program. This study aimed to analyze the influence of management functions, including planning, organizing, implementation, and controlling, on outpatient satisfaction among BPJS participants at Mina Hajj Hospital Medan. This study employed a quantitative approach with a cross-sectional design. A total of 100 respondents were selected using an accidental sampling technique. Data were collected through structured questionnaires that had been tested for validity and reliability. Data analysis was conducted using multiple logistic regression tests. The results showed that all management functions had a significant effect on patient satisfaction (p < 0.05). Among these variables, service implementation was identified as the most dominant factor influencing patient satisfaction, with an odds ratio (OR) value of 445.949. This finding indicates that service delivery that is in accordance with procedures, fast, accurate, and communicative plays a crucial role in improving patient satisfaction. The study concludes that structured service management, patient-oriented approaches, and continuous evaluation and supervision are essential to improving hospital service quality. Therefore, strengthening the implementation and organizing functions should become a priority in efforts to enhance healthcare service quality in hospitals.